Research on the Integrated Application of Computer Technology and Information Management - Men, Xiaoshuang (Transactions on Economics, Business and Management Research, 2024)
With the continuous improvement of our country’s technological level, computer technology has been widely applied in various fields and has achieved significant results. Integrating computer application technology with information management is not only a fusion at the technological level but also an innovation in management models. By deeply integrating computer technology into the information management process, efficient collection, storage, processing, and sharing of information can be achieved, thereby breaking down information barriers between departments and promoting the circulation and collaboration of internal information within enterprises. In the specific integration and application process, it is necessary to first enhance information management awareness, gradually expand information collection channels, and build a comprehensive information management system in line with actual development situations. Through the integrated application of computer application technology and information management, the optimization of information resources and their efficient utilization can be realized, enhancing the competitiveness of enterprises. This also lays a solid foundation for enterprises’ digital transformation and intelligent upgrading, pushing enterprises to advance to higher levels of development. Therefore, this integration process must be highly valued, continuously explored, and innovated to promote the sustainable and healthy development of enterprises.